The superstar effect in Tennis - Creutzburg, Carsten (Universität Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2024)
This study is the first to investigate the superstar effect on professional men's tennis players' situational performance, employing novel serve and return ratings. We innovate by examining the impact of superstars on the performance of both higher-ranked (HR) and lower-ranked (LR) players. We provide evidence that HR players deliberately increase/decrease their performance in (non)dominant match situations based on their rank and the timing of facing a superstar in subsequent matches. Similarly, there are differences in the extent of performance shifts induced by superstars among different rank groups for LR players; however, the differences do not extend to different within-match situations.
10419/302868
Keywords: Graue Literatur; Superstar effect; tournaments; professionals; productivity